Digitalisasi Digitalisasi Pertanian Melalui Platform Online untuk Meningkatkan Pendapatan KWT Sedap Malam - Ratu Chaterine Fajri Ratu; Dini Safitri; Putri Irmala Sari; Supri Yanto; Valdi Mughni Budiman; Winda Kartika (JURNAL ABDIMAS DOSMA (JAD), 2025)
Agricultural digitalization has become a strategic step in enhancing the competitiveness and income of farmers in the digital era. The method was used in participatory action, involving 25 members of the Sedap Malam KWT. The training is conducted in three stages: introduction to the concept of digital marketing, practical use of e-commerce platforms, and evaluation of online sales results. Data collection techniques include observation, interviews, and analysis of sales reports during the month prior to the training. The results of the dedication show a significant increase in the average income of KWT members by 66,87% after implementing online marketing strategies. In addition, digital literacy among participants increased by 90,83%. Therefore, agricultural product marketing training through online platforms is effective in increasing the income and digital capacity of the Sedap Malam KWT. This dedication recommends the expansion of similar programs to other farmer groups to encourage digital transformation in the agricultural sector.